SPEECH ACT IMPERATIVE IN TEACHING ENGLISH ON PGSD STUDENTS - dayu retno puspita; Agus Sulaiman (STIBA IEC JAKARTA, 2017)
This research analyzes Lecturer's Imperative Teaching in teaching English to PGSD students at Muhammadiyah University of Tangerang. Aspects analyzed include the form of speech acts and the meaning of speech acts imperative contained in teaching English. This research uses descriptive method. Data collection techniques used in this study is a recording technique. Researchers record conversations conducted between lecturers and students. This research data comes from conversations between lecturers and students of PGSD. The result of the research shows that politeness strategy applied in English language teaching especially in PGSD student of 6th semester English Course at Muhammadiyah University Tangerang is a strategy of politeness of context. The context found is the compassion of imperative speech acts in the form of forcing, inviting, and pleading with the discovery of three of the four functions of language according to Leech (1993: 162), ie competitive, convivial, and collaborative. However, the commonly used language function is the collaborative language function. The success rate of use of imperative speech acts is very effective in teaching English so that learning can be done well.